How to engage the right brain hemisphere in aphasics without even singing: evidence for two paths of speech recovery - Stahl, Benjamin; Henseler, Ilona; Turner, Robert; Geyer, Stefan; Kotz, Sonja A. (Frontiers in Human Neuroscience, 2013)
There is an ongoing debate as to whether singing helps left-hemispheric stroke patients recover from non-fluent aphasia through stimulation of the right hemisphere. According to recent work, it may not be singing itself that aids speech production in non-fluent aphasic patients, but rhythm and lyric type. However, the long-term effects of melody and rhythm on speech recovery are largely unknown. In the current experiment, we tested 15 patients with chronic non-fluent aphasia who underwent either singing therapy, rhythmic therapy, or standard speech therapy. The experiment controlled for phonatory quality, vocal frequency variability, pitch accuracy, syllable duration, phonetic complexity and other influences, such as the acoustic setting and learning effects induced by the testing itself. The results provide the first evidence that singing and rhythmic speech may be similarly effective in the treatment of non-fluent aphasia. This finding may challenge the view that singing causes a transfer of language function from the left to the right hemisphere. Instead, both singing and rhythmic therapy patients made good progress in the production of common, formulaic phrases—known to be supported by right corticostriatal brain areas. This progress occurred at an early stage of both therapies and was stable over time. Conversely, patients receiving standard therapy made less progress in the production of formulaic phrases. They did, however, improve their production of non-formulaic speech, in contrast to singing and rhythmic therapy patients, who did not. In light of these results, it may be worth considering the combined use of standard therapy and the training of formulaic phrases, whether sung or rhythmically spoken. Standard therapy may engage, in particular, left perilesional brain regions, while training of formulaic phrases may open new ways of tapping into right-hemisphere language resources—even without singing.